Анна Каренина: [роман] / Лев Толстой - Толстой Лев Николаевич (Лучшая мировая классика, 2022)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 56913 / Цена: 202.30 / Сис.шифр: 84(2=411.2) / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)-44